IMPLEMENTASI PENDEKATAN KONTEKSTUAL DALAM MENINGKATKAN KETERAMPILAN MENULIS SISWA KELAS IV SDIT AROFAH 2 KLEGO - Septiani, Vicky; Muchamad Kamil, Achmad (At-Taksis: Jurnal Pendidikan Dasar PGMI STAI Sangatta, 2024)
The Contextual Approach (Contextual Teaching and Learning/CTL) is a learning concept that links subject matter to students' life situations. This article discusses the meaning, components, principles and steps for implementing CTL. CTL components include meaningful relationships, meaningful work, self-regulated learning, collaboration, critical and creative thinking, individualized service, achievement of high standards, and authentic assessment. The principles include constructivism, discovery, inquiry, learning communities, modeling, reflection, and real assessment. The implementation steps include developing students' independent thinking, inquiry, questioning, forming a learning community, modeling, reflection, and authentic assessment. With CTL, learning becomes more relevant, provides meaningful experiences, and develops students' skills in critical thinking, collaboration, and achieving high learning standards.